The Life of Euphrosyne of Polotsk in Synaxarion Manuscript from Lviv Historical Museum - Zhurina, Yulia (Slavistica Vilnensis, 2020)
This publication is dedicated to a newly discovered copy of the synaxarian life of St. Euphrosyne of Polotsk kept in the Lviv Historical Museum (the 17th c. manuscript No. 108). A synaxarian (brief) version of the life of St. Euphrosyne was previously known in four 15th–17th centuries handwritten synaxaria for the spring half of a year. The information of the fifth copy of St. Euphrosyne’s of Polotsk life has been provided and its text is published.